Pemberdayaan Perempuan oleh Kelompok Wanita Tani The Ampale Star Nagari Taratak Kecamatan Sutera Kabupaten Pesisir Selatan - Yanti, Febri; Fatmariza, Fatmariza; Montessori, Maria; Mochtar, Henni (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This research endeavors to delineate the empowerment of women facilitated by the Farmer Women's Groups, known as The Ampale Star, located in Nagari Taratak, Pesisir Selatan District. The study is motivated by the dearth of employment opportunities for women within this district. Employing a qualitative descriptive approach, informants were selected using purposive sampling techniques. Data collection encompassed interviews, documentation, and observation, with data validity assured through triangulation. Analysis involved data collection, reduction, presentation, and drawing conclusions. The initiatives undertaken by KWT The Ampale Star encompass: (1) providing plant seed assistance from governmental and private sources, (2) imparting agricultural cultivation skills, (3) processing and marketing corn juice milk, and (4) furnishing assistance with processing and cultivation equipment. Factors facilitating women's empowerment include strong spousal support, adequate facilities and materials, collaboration with relevant agencies, and positive community backing. Conversely, inhibiting factors include women's occasional reluctance to attend meetings, concurrent organizational commitments, childcare responsibilities, underdeveloped human resources among women farmers, and educational limitations hindering skill refinement and discussion participation.